Objective assessment of the damaging effect of glucocorticoids (toxicity index) in patients with systemic lupus erythematosus - N. Yu. Nikishina; E. V. Ermolaeva; A. A. Mesnyankina; E. A. Aseeva; S. K. Soloviev; B. Sh. Isaeva; G. M. Koylubaeva; A. M. Lila (Современная ревматология)
Systemic lupus erythematosus (SLE) is a multisystem disease characterized by chronic inflammation and damage to vital organs and systems. Despite the great success achieved in the treatment of SLE, glucocorticoids (GC) remain one of the main methods of therapy. The GC toxicity index is an objective method for assessing adverse events associated with their use, and in future studies can be actively used to monitor the safety of various therapy regimens. Wider introduction of this index in the management of patients with SLE will allow to optimize approaches to the selection of GC doses, to consider earlier prescription of biologic disease modifying antirheumatic drugs, before the development of severe irreversible damage.